(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A new series of 2, 5 di-substituted benzimidazole derivatives have been synthesized. The structures of the synthesized compounds were confirmed by IR, 1H NMR and Mass spectral analysis and they were evaluated for their antibacterial; Proteus vulgaris (NCTC 4635), Klesibella pneumonia (ATCC 29655), Bacillus cereus (NL98), and Enterococcus faecium (ATCC 29212) and antifungal (Aspergillus niger and Aspergillus fumigatus) activities by disc diffusion method. All of the synthesized compounds showed good antibacterial and antifungal activity. However the antibacterial and antifungal activity of the synthesized compounds against the tested organisms was found to be less than that of respective standard drug at tested dose level.